Interfacial activity of modified dextran polysaccharide to produce enzyme-responsive oil-in-water nanoemulsions. Issue 37 (7th April 2021) - Navascuez, Marcos; Gracia, Raquel; Marradi, Marco; Díaz, Natividad; Rodríguez, Javier; Loinaz, Iraida; López-Gállego, Fernando; Llop, Jordi; Dupin, Damien
Abstract : The slight modification of dextran polysaccharides offers a new family of enzyme-responsive emulsifier for encapsulation and controlled release of hydrophobic molecules. Abstract : Herein, we report the evaluation of dextran (DXT) derivatives bearing hydrophobic or hydrophilic functional groups as stabilisers of oil-in-water (O/W) emulsions. All investigated modifications conferred interfacial activity to produce stable O/W emulsions, methacrylate(MA)-functionalised DXT being the most promising stabiliser. A minimum amount of MA was required to obtain stable O/W nanoemulsions, which could be degraded in the presence of lipases.